The Case for Offering Psychosocial Support to Staff and Students in Higher Education - Karapejovski, Boban; Oncevska-Ager, Elena; Kitanovska-Kimovska, Sonja; Tasevska Hadji-Boshkova, Iskra; Maleska, Kalina (Blaze Koneski Faculty of Philology, 2023)
This paper looks at aspects of professional wellbeing addressed by a project we designed and ran in our roles as members of the Committee for Enhancing the Quality of Teaching at Blaže Koneski Faculty of Philology (Saints Cyril and Methodius University, North Macedonia). First, we present findings on the impact of the current COVID-19 pandemic on the students’ and teachers’ psychological wellbeing to stress the necessity of providing psychosocial support to both groups. Then, we forge links between professional wellbeing on the one hand, and educational psychology and educational philosophy on the other hand, in order to highlight the centrality of wellbeing to performing well in any job, including in academia. We go on to discuss the project design and the feedback we received from some of the project participants. We discuss the findings and make recommendations for the future.
Keywords: psychosocial support, teacher wellbeing, student wellbeing, tertiary education